Systemic Identification of Hevea brasiliensis EST-SSR Markers and Primer Screening. (23rd January 2017) - Hou, Benjun; Feng, Suping; Wu, Yaoting
Abstract : This research aimed to systematically identify and preliminarily validate the Hevea brasiliensis expressed sequence tag (EST) information using Simple Sequence Repeat (SSR) and provide evidence for further development of SSR molecular marker. The definition of general SSR features of Hevea EST splicing sequences and development of SSR primers founded the basis of diversity analysis and variety identification for Hevea tree resource. 1134 SSR loci were identified in the EST splicing sequence and distributed in 840 Unigene. The occurrence rate of SSR loci was 23.9%, and the average distribution distance of EST-SSR was 2.59 kb. The major repeat type was mononucleotide repeat motif, which accounted for 38.89%, while the corresponding value was 36.95% for dinucleotide repeat motif and 18.17% for trinucleotide repeat motif; the proportion of other motifs was only 5.99%. The superior repeat motifs for mononucleotide, dinucleotide, and trinucleotide were A/T, AG/CT, and AAG/CTT, respectively. 739 pair of primers were designed for 1134 SSR loci. PCR amplification was performed on Hevea Reyan5-11, Reyan87-6-47, and PR107, and 180 pairs of primers were selected which were able to amplify polymorphism bands.